دراسة إمكانيّة الانتقال من الصيغة البريدية نحو الصيغة البنك يّة لتعزيز الشّمول المالي 6 حالة تونس: Studying the possibility of shifting from postal formula to banking nature to promote financial inclusion: The case of Tunisia - بوزانة أيمن; حمدوش وفاء (Journal of North African Economies, 2025)
This study aimed to discuss the possibility of shifting from the postal formula to banking nature in order to promote financial inclusion under the limited levels of the main index of financial inclusion in Tunisia in 2014 and 2017. To answer the problem at hand, we have relied on the analytical descriptive approach, focusing on identifying the most significant factors that encourage to strengthen the financial inclusion strategy in Tunisia. The study concluded that the transition from postal to banking is taking its first steps in the Tunisian banking environment by launching a national strategy for financial inclusion and a series of enhanced initiatives for the idea of a post-bank project. Although there are many private and public factors encouraging the reflection of the project, there are many difficulties for postal institutions to shift towards banking activity.